Implementace informačního systému - Škrabálek, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Diplomová práce se zabývá implementací informačního systému pro operativní řízení malé strojírenské firmy se zaměřením na zakázkovou výrobu. V práci je popsán současný stav řízení výroby bez podpory informačního systému. Na základě zjištěných nedostatků jsou vypsány požadavky a kritéria na nový informační systém. Poté je rozebrán výběr informačního systému a jeho implementace v průběhu výroby. V závěru práce je popsáno řízení výroby s podporou zvoleného informačního systému a ekonomické zhodnocení na pořízení informačního systému.

This diploma thesis deals with the implementation of an information system for the operational management of small engineering companies with a focus on custom manufacturing. The thesis describes the current state of production control without support of the information system. Based on the identified shortcomings, the requirements and criteria for the new information system were developed. Then the selection of the information system and its implementation during production is dissected. At the end of the thesis there is described the production control with the support of the selected information system and the economic evaluation for acquisition of the information system.
Implementation of information system
Keywords: implementace; ERP systém; výroba; plánování; organizování; implementation; ERP system; production; planning; organization